Does parental education affect fertility? Evidence from pre-demographic transition Prussia - Sascha O. Becker; Francesco Cinnirella; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
While women's employment opportunities, relative wages, and the child quantity-quality trade-off have been studied as factors underlying historical fertility limitation, the role of parental education has received little attention. We combine Prussian county data from three censuses - 1816, 1849, and 1867 - to estimate the relationship between women's education and their fertility before the demographic transition. Despite controlling for several demand and supply factors, we find a negative residual effect of women's education on fertility. Instrumental-variable estimates, using exogenous variation in women's education driven by differences in landownership inequality, suggest that the effect of women's education on fertility is causal.
Keywords: N33; J13; J24; 330; demographic transition; female education; fertility; nineteenth century Prussia; Frauenbildung; Fruchtbarkeit; Demographischer Übergang; Schätzung; Preußen